Sendratari Rara Jonggrang Dalam Perspektif Koreografis dan Pariwisata - Hersapandi, Hersapandi (PANGGUNG, 2017)
ABSTRACT "The Rara Jonggrang Ballet" was a dance drama without dialogue that took the story of the legend of Prambanan temple. This choreography tourist art was created as an alternative travel destination renewable tourist performing arts in Yogyakarta. The logic of economic law of supply and demand of the total number of tourists visiting Prambanan temple for 2.992 person/day was a business opportunity creatively to improve the economic viability and competitiveness forces of the nations comparative advantage and competitive choreography art of travel was believed to be the new icon of the tourist attraction in attractions Prambanan temple. The creative process of creation ballet Rara Jonggrang (cultural creativity) and the creative process in the economy (economic creativity) was a strategic part in building a creative economy based on the values of local wisdom, thus contributing to the strengthening of the economy of traditional arts and community supporters.Keywords: ballet, choreography, art, travel, management, creative economyABSTRAKâSendratari Rara Jonggrangâ adalah drama tari tanpa dialog yang mengambil cerita dari legenda candi Prambanan. Koreografi seni wisata ini dicipta sebagai alternatif destinasi seni pertunjukan wisata terbarukan di Yogyakarta. Logika hukum ekonomi antara permintaan dan penawaran dari jumlah angka kunjungan wisatawan ke candi Prambanan sebesar 2.992 orang/hari merupakan peluang bisnis kreatif untuk meningkatkan kemampuan ekonomi dan kekuatan daya saing bangsa. Keunggulan komparatif dan kompetitif koreografi seni wisata ini diyakini dapat menjadi ikon baru daya tarik wisatawan di objek wisata candi Prambanan. Proses kreatif penciptaan sendratari Rara Jonggrang (kreativitas budaya) dan proses kreatif dalam perekonomian (kreativitas ekonomi) merupakan bagian strategis dalam membangun ekonomi kreatif yang berbasis pada nilai-nilai kearifan lokal, sehingga memberi kontribusi bagi penguatan seni tradisi dan ekonomi masyarakat pendukungnya.Kata kunci: sendratari, koreografi, seni wisata, manajemen, ekonomi kreatifÂ